Essential Oil Analysis of Illicium anistum L. Extracts - Min, Hee-Jeong; Kim, Chan-Soo; Hyun, Hwa-Ja; Bae, Young-Soo (Journal of the Korean Wood Science and Technology, 2017)
Fresh japanese anise (Illicium anisatum L.) tree leaves were collected and ground after drying. The essential oils of the leaves were analyzed by gas chromatography-mass spectrometry (GC-MS) using headspace (HS) and solid phase-microextra (SPME) methods. Volatile components of the leaves were identified 21 and 65 components in HS and SPME, respectively. The main components of the essential oils obtained by HS method were eucalyptol (36.7%), (+)-sabinene (15.61%), δ-3-carene (6.87%), α-pinene (6.07%), γ-terpinen (5.72%), α-limonene (5.26%), β-myrcene (4.13%), α-terpinene (4.04%) and β-pinene (3.73%). The other components were less than 3.5%. SPME method also showed that eucalyptol (17.88%) was main. The other were 5-allyl-1-methoxy-2 (13.29%), caryophyllene (6.09%), (+)-sabinene (5.60%), α-ocimene (4.89%) and β-myrcene (3.73%), and the rest were less amounts than 3.5%. This work indicated that many more volatile components were isolated, comparing to the previous literature data and that SPME method was much more effective than HS method in the analysis of the volatile components. KCI Citation Count: 4